Applying standard work in a paint shop of wood furniture plant: a case study - Ribeiro, Luís (2013)
This paper reports the process of implementation of a standard work program at Swedwood Board on Frame (BOF) paint shop by applying a number of lean techniques. Following the identification of waste on the operations, through a detailed analysis of the shop-floor, and identification of use of uneven work standards among the work teams, some Lean techniques were applied to stabilize the process for subsequent implementation of standard work procedures. These techniques, e.g. 5S, visual management, poka-yoke, quick-fit mechanisms, among others, aimed: 1) the reduction of the defects, rework and scrap rates; 2) reduction of changeovers; and 3) reduction of the number of production halts. The standard work program that followed aimed the overall improvement of the process efficiency, rapid identification of anomalies and improved problem solving capability. The results achieved included: the reduction of defects by about 27%; the rework rate dropped 33% and the scrap rate dropped 31%; improvements to the production efficiency by 14%; along with reduction on the need for extra work hours and increased versatility of the operators.